PRODUCTION PERFORMANCE OF TANUVAS NAMAKKAL GOLD JAPANESE QUAIL FED DIET WITH DIFFERENT LEVELS OF ENERGY AND LYSINE - K. Shibi Thomas; R. Amutha; M. R. Purushothaman; P. N. Richard Jagatheesan; S. Ezhil Valavan (Indian Journal of Veterinary and Animal Sciences Research, 2025)
A biological trial was conducted with “TANUVAS Namakkal gold Japanese quail” to determine the optimum level of energy and lysine requirement on the production performance during the chick and grower phase. Seven hundred and twenty, straight-run, day-old chicks were randomly grouped in nine treatments with four replicates of twenty chicks each. Three levels of energy (2800, 2900 and 3000 kcal/kg) and three levels of lysine (1.2, 1.3 and 1.4%) were used in a 3 x 3 factorial design. Low energy (2800 kcal/kg) had significant (P